Changes in Functional Compounds, Volatiles, and Antioxidant Properties of Culinary Herb Coriander Leaves (Coriandrum sativum) Stored Under Red and Blue LED Light for Different Storage Times - Shoko, Tinotenda; Manhivi, Vimbainashe E.; Mtlhako, Malebo; Sivakumar, Dharini (Frontiers in Nutrition, 2022)
This study evaluated the influence of red (630–640 nm) and blue (450 nm) light-emitting diodes (LED) lights on the changes of antioxidant constituents, activity, volatile compounds and overall acceptability of Coriander leaves (Coriandrum sativum L.) during postharvest storage. Coriander leaves harvested at commercial maturity, packed in polyethylene terephthalate punnets, and exposed for 2 h to red LED or blue LED lights separately during storage at 5°C and 85% RH up to 9 days. Coriander leaves exposed to white light (2 h) and continuous darkness served as controls. Samples were removed from cold storage at 3, 6 and 9 days to determine the antioxidant constituents, and their activity, retention of volatile compounds and overall acceptance. The β-carotene content peaked 15 by 44.55% on day 6 in coriander leaves exposed to the red LED light. However, leaves exposed to blue and red LED light showed an increase of total phenolic content by 9.34% and 6.39% on day 9 respectively. Exposure to blue LED lights increased the antioxidant activities (DPPH, ABTS and FRAP), quercetin content and the concentration of typical coriander aroma, 2-tridecenal, 2-dodecenal, (E) and Z-9- 19 hexadecenal on day 9. Coriander leaves exposed to blue LED light (2 h) and stored up to day 9 scored a higher acceptance level by the panelists. Thus blue light LED treatment during postharvest storage can be recommended retain the antioxidant property of coriander leaves.